2019
DOI: 10.22216/jen.v4i1.3505
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Seduhan Zingiber Offcinale (Jahe) Terhadap Penurunan Emesis Gravidarum

Abstract: <p><em>Emesis Gravidarum is a many that occur to pregnant woman in Indonesian. Emesis graviadarum can cause disturbed the daily activities of pregnant woman, also can decrease appetite and dehydration. When don’t overcome than the hiperemesis gravidarum, can be resolve with non pharmacology therapy, which one non pharmacology therapy is ginger. Ginger consist gingerol Shogaol, and zingeberen that can be decrease nausea and vomiting to pregnant woman. This research aims to know the effective of stee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 0 publications
1
2
0
3
Order By: Relevance
“…In addition, the fetus is at risk of being born with low birth weight to death . 14 In accordance with Mutmainna's research that Hyperemesis gravidarum is the determinant of the occurrence of LBW by 4,821.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…In addition, the fetus is at risk of being born with low birth weight to death . 14 In accordance with Mutmainna's research that Hyperemesis gravidarum is the determinant of the occurrence of LBW by 4,821.…”
Section: Resultssupporting
confidence: 68%
“…From a total population of 39 (79.5%) pregnant women experienced emesis according to a study conducted from 108 pregnant women, 74% reported nausea, although only 1.8% experienced it as a symptom that only occurred in the morning. As many as 27% of pregnant women who experienced nausea and vomiting said their symptoms disappeared by the twelfth week, although most felt better by the 22nd week of pregnancy 14 The average emesis gravidarum of pregnant women with TM I before being given acupressure therapy at the Seyegan Health Center with a mean of 10.4 and a standard deviation of 1.029. In line with what was stated that nausea (nausea) and vomiting (emesis) are normal symptoms and are often found in the first trimester of pregnancy.…”
Section: Resultsmentioning
confidence: 99%
“…Analisis data menggunakan uji t sampel berpasangan menghasilkan nilai p sebesar 0,000 (p < 0,05), dapat disimpulkan bahwa seduhan jahe efektif untuk mengurangi rasa mual di awal kehamilan. (Rufaridah, Herien, dan Mofa, 2019) Perbedaan dengan penelitian ini yaitu penelitian sebelumnya menggunakan seduhan jahe hangat yang diberikan selama selama 4 hari dalam satu minggu, sedangkan peneliti menggunakan rebusan jahe merah dengan gula aren dan diberikan selama 7 hari.…”
Section: Hasil Dan Pembahasanunclassified
“…Gingerol and other components of ginger are known to have anti-hydroxytryptamine activity through experiments on the ileum. Galanolactone, another ingredient in ginger, is a competitive antagonist to the ileus -HT receptor, which exerts anti-emetic effects (Rufaridah et al, 2019).…”
Section: Effect Of Ginger Brewing On Emesis Gravidarummentioning
confidence: 99%